2019
DOI: 10.1111/jen.12693
|View full text |Cite
|
Sign up to set email alerts
|

Modelling time‐varying low‐temperature‐induced mortality rates for pupae of Tuta absoluta (Gelechiidae, Lepidoptera)

Abstract: In a series of laboratory experiments, acclimated pupae of Tuta absoluta were exposed to various constant low temperatures in order to estimate their maximum survival times (Kaplan–Meier, Lt99.99). A Weibull function was fitted to the data points, describing maximum survival time as a function of temperature. In another experiment at −6°C, the progress of mortality increasing with exposure time was identified. These values were fitted by a sigmoidal function converging asymptotically to 100% mortality for very… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…When the exposure duration was longer than 4 h, the pupal stage recorded the lowest Ltemp 90 compared to the other life stages, indicating a higher cold tolerance capacity of pupae during long-term low temperature stress. This is consistent with the results reported by Kahrer et al (2019), who found that T. absoluta pupae were the most frost-resistant compared to other developmental stages of the species at − 4 °C. However, results from Van Damme et al (2015) showed that adults had the highest cold tolerance compared to larvae and pupae at 5 °C, but the survival was not significantly influenced by its developmental stage at 0 °C.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…When the exposure duration was longer than 4 h, the pupal stage recorded the lowest Ltemp 90 compared to the other life stages, indicating a higher cold tolerance capacity of pupae during long-term low temperature stress. This is consistent with the results reported by Kahrer et al (2019), who found that T. absoluta pupae were the most frost-resistant compared to other developmental stages of the species at − 4 °C. However, results from Van Damme et al (2015) showed that adults had the highest cold tolerance compared to larvae and pupae at 5 °C, but the survival was not significantly influenced by its developmental stage at 0 °C.…”
Section: Discussionsupporting
confidence: 93%
“…It was assumed that the low temperatures during winter in newly invaded areas would prevent invasive species from successful overwintering (Kahrer et al 2019). Xinjiang is one of the regions in China that suffer very harsh winter, with the lowest temperatures recorded between − 10 and − 30 °C (Hu 2014). Consequently, understanding the cold tolerance of T. absoluta is crucial for evaluating its dispersal potential in this province.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During adverse weather conditions (for instance during winter), abiotic factors are unfavorable and tomato plants become scarce forcing SATP to adopt diverse strategies to survive (Nyamukondiwa et al., 2013; Van Damme et al., 2015; Machekano et al., 2018; Cherif et al., 2019; Kahrer et al., 2019; Tarusikirwa et al., 2020; Campos et al., 2021). These strategies have been extensively studied, including facultative diapause and survival of pupae in temperatures below critical thresholds for SATP development (Van Damme et al., 2015; Kahrer et al., 2019; Campos et al., 2021). Prior studies have not provided information on the survival of SATP at 4 °C for various exposure periods on alternative host plants.…”
Section: Discussionmentioning
confidence: 99%
“…8). e Temperaturedependent mortality (data from Van Damme et al 2015;Krechemer and Foerster 2015;Martins et al 2016;Kahrer et al 2019) with the line indicating the fitted polynomial function used in the model…”
Section: Methodsmentioning
confidence: 99%